Clinical application of long‐read nanopore sequencing in a preimplantation genetic testing pre‐clinical workup to identify the junction for complex Xq chromosome rearrangement‐related disease. (24th February 2023) - Mariya, Tasuku; Shichiri, Yui; Sugimoto, Takeshi; Kawamura, Rie; Miyai, Syunsuke; Inagaki, Hidehito; Sugihara, Eiji; Ikeda, Keiko; Baba, Tsuyoshi; Ishikawa, Aki; Ammae, Michiko; Nakaoka, Yoshiharu; et al.
Abstract: Objective: Xq chromosome duplication with complex rearrangements is generally acknowledged to be associated with neurodevelopmental disorders, such as Pelizaeus‐Merzbacher disease (PMD) and MECP2 duplication syndrome. For couples who required a PGT‐M (pre‐implantation genetic testing for monogenic disease) for these disorders, junction‐specific PCR is useful to directly detect pathogenic variants. Therefore, pre‐clinical workup for PGT‐M requires the identification of the junction of duplicated segments in PMD and MECP2 duplication syndrome, which is generally difficult. Methods: In this report, we used nanopore long‐read sequencing targeting the X chromosome using an adaptive sampling method to identify breakpoint junctions in disease‐causing triplications. Results: By long‐read sequencing, we successfully identified breakpoint junctions in one PMD case with PLP1 triplication and in another MECP2 triplication case in a single sequencing run. Surprisingly, the duplicated region involving MECP2 was inserted 45 Mb proximal to the original position. This inserted region was confirmed by FISH analysis. With the help of precise mapping of the pathogenic variant, we successfully re‐established STR haplotyping for PGT‐M and avoided any potential misinterpretation of the pathogenic allele due to recombination. Conclusion: Long‐read sequencing with adaptive sampling in a PGT‐M pre‐clinical workup is a beneficial method for identifying junctions of chromosomal complex structural rearrangements. Key points: What's already known about this topic? For couples who required a PGT‐M (pre‐implantation genetic testing for monogenic disease) for diseases with complex chromosomal structural rearrangements, junction‐specific PCR is useful to directly detect pathogenic variants. Therefore, pre‐clinical workup for PGT‐M requires the identification of the junction of duplicated segments in Pelizaeus‐Merzbacher disease (PMD) and MECP2 duplication syndrome, which is generally difficult and often takes a long time. What does this study add? By long‐read sequencing, we successfully identified breakpoint junctions in one PMD case with PLP1 duplication and in another MECP2 duplication case in a targeted sequencing with the adaptive sampling method. Complex chromosomal rearrangements may cause an unexpected misdiagnosis in haplotype analysis if the STR/SNP marker is set around the original position of the pathogenic variants. Clinicians should try to detect pathogenic structural variants per se as much as possible as part of a PGT‐M preclinical workup, and long‐read sequencing may be a useful tool for this purpose.